INDIVIDUAL WORK WITH STUDENTS - Karimjanov A. (Web of Journals Publishing, 2024)
The article reflects the content, essence, goals, and objectives of individual education conducted with pupils and students in educational institutions.
Keywords: Management, leadership, current, staff, independence, modern, mature, contemporary, system, school, family, community, modernization, science, technique and technology, method combination.